Iodine supplementation of lactating women and assessment of infant visual information processing and maternal and infant thyroid function: A randomized trial - Gebreegziabher, Tafere (PLoS One, 2019)
Iodine deficiency is one of the major causes of brain damage in childhood. However, iodine supplementation during early pregnancy and lactation can prevent the ill effects of iodine deficiency. This study evaluated maternal and infant thyroid function and infant visual information processing (VIP) in the context of maternal iodine supplementation. A community-based, randomized, supplementation trial was conducted. Mother infant dyads (n = 106) were enrolled within the first 10 days after delivery to participate in this study. Mothers were randomly assigned either to receive a potassium iodide capsule (225 μg iodine) daily for 26 weeks or iodized salt weekly for 26 weeks. Maternal thyroxine (T(4)), triiodothyronine (T(3)), thyroid stimulating hormone (TSH), thyroglobulin (Tg), urinary iodine concentration (UIC), breast milk iodine concentration (BMIC) and infant T(4), TSH, UIC and VIP were measured as outcome variables. At baseline, neither mothers nor infants in the two groups were significantly different in any of the biomarkers or anthropometric measurements. Maternal TSH and goiter prevalence significantly decreased following iodine supplementation. The percentage of infants who preferentially remembered the familiar face was 26% in the capsule and 51% in the I-salt groups. Infant sex, length for age Z score, BMIC, maternal education and household food security were strong predictors of novelty quotient. In conclusion supplementation daily for six months with an iodine capsule or the use of appropriately iodized salt for an equivalent time was sufficient to reduce goiter and TSH in lactating women. Higher BMIC and LAZ as well as better household food security, maternal education, and male sex predicted higher novelty quotient scores in the VIP paradigm.